Groundswell Africa : A Deep Dive Into Internal Climate Migration in Uganda - Rigaud, Kanta Kumari (World Bank, Washington, DC, 2021)
Uganda is a diverse and verdant country. From the tall volcanic mountains along the eastern and western borders to the densely forested wetlands of the Albert Nile River and the rainforests in the center of the country, it encompasses many different ecosystems. Kampala, the capital city, is built around seven hills not far from the shores of Lake Victoria. These varying landscapes provide Ugandans with ample resources to capitalize on tourism and cultivate crops, including Ugandan coffee, which has become a favorite of coffee drinkers around the world. These rich and beautiful landscapes, however, are under threat from climate change, which could have disastrous effects for Ugandans. This report shows that by 2050, as many as 12 million people, or 11 percent of the population could move within Uganda because of slow onset climate factors, without concrete climate and development action. Immediate, rapid, and aggressive action on the cutting down emissions as a global community and pursuing inclusive resilient development at the national level could bring down this scale of climate migration by about 35 per cent. Contextualizing the results from an innovative climate migration model applied to Lake Victoria Basin countries, it finds that such climate-induced migration, if unattended, may deepen existing vulnerabilities across the country, potentially leading to greater poverty, fragility, and conflict. As lives, livelihoods, and the economy are integrally linked to the environment, addressing climate change is an imperative for Uganda. Adopting inclusive development policies that reduce greenhouse gas emissions and integrate climate resilience could decrease the number of internal migrants significantly. Acting early and focusing on improved management of forest and other landscapes, developing local job opportunities, and providing basic services for both host communities and refugees will be important to help these communities survive and thrive in a changing climate. The right mix of policies would also encourage the ingenuity and energy of Uganda’s youthful population, which is projected to almost triple by 2050.